(untitled) (International Journal of Engineering and Computer Science, 2021)
The purpose of this study is to analyze the vibration displacement on fiberglass reinforced plastic beams with variations a number of fibers in the resin matrix. Composite beams was made of fiberglass and polyester resin matrix with a number of fiberglass: 0, 24, and 48. Composite beams was manufactured by hand lay-up method with the unidirectional fiber orientation. The composite beams used have the dimension of length: 500 mm, height: 20 mm, and width: 20 mm. During the experimental test, the beam was vibrated using an exciter motor which was placed at the end of the cantilever support then using a vibration meter, the vibration displacement data (mm) was measured by placing the vibration transducer postions : 50 mm, 250 mm, and 450 mm from the cantilever support. During the vibration test, the vibration displacement data on the vibration meter screen were recorded using a camera recorder and the data was taken 6 times at each of measurement points. The experimental and analysis results show that the value of vibration displacement (mm) decreases when the fiberglass is added to the composite beam, or in other words, the addition of fiberglass provides an increase in the ability of the beam to withstand vibrations. The maximum vibration displacement value on composites with 0 fiberglass: 0.641 mm, then the vibration displacement decreased in composites with 24 fiberglass: 0.506 mm and the lowest displacement value for the composites with 48 fiberglass: 0.395 mm. Whereas for 3 measurement points at positions 5 cm, 25 cm, and 45 cm along the beam for three kind of the composites, the maximum value of vibration displacement value was obtained at the end of beam composites or at 45 cm from cantilever support: 0.735 mm on composite beam with 0 fiberglass and minimum at position 5 cm near the cantilever support with the value of vibration displacement: 0.323 mm on composite beam with 48 fiberglass.